2004
DOI: 10.1093/jn/134.4.762
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling in Human Preadipocytes and Adipocytes by Microarray Analysis

Abstract: Uncontrolled expansion of adipose tissue leads to obesity, a public health epidemic affecting >30% of adult Americans. Adipose mass increases in part through the recruitment and differentiation of an existing pool of preadipocytes (PA) into adipocytes (AD). Most studies investigating adipogenesis used primarily murine cell lines; much less is known about the relevant processes that occur in humans. Therefore, characterization of genes associated with adipocyte development is key to understanding the pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
69
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 48 publications
11
69
0
1
Order By: Relevance
“…40 It is likely that higher expression of SHMT2 in adipocytes is related to increased mitochondrial density. The relative small differences agree with previous studies 41,42 but may in part also be due to the selection of genes used, which was directed at white adipose characteristics and not to identify differences between white and brown adipose tissues. LiSa-2 and PAZ6 are both used to study adipocyte function, [8][9][10] but have a different physiological background.…”
Section: Discussionsupporting
confidence: 89%
“…40 It is likely that higher expression of SHMT2 in adipocytes is related to increased mitochondrial density. The relative small differences agree with previous studies 41,42 but may in part also be due to the selection of genes used, which was directed at white adipose characteristics and not to identify differences between white and brown adipose tissues. LiSa-2 and PAZ6 are both used to study adipocyte function, [8][9][10] but have a different physiological background.…”
Section: Discussionsupporting
confidence: 89%
“…41) It was also reported that expression of Smarcb1 was increased in human adipocytes compared with that in preadipocytes. 42) However, at the present, the functions of Ddx5 and Smarcb1 in adipogenesis, as well as that of glutathione S-transferase w1 (GSTw1), remain unclear. It was reported that HIF-3a is induced during differentiation of cardiac cells and alveolar type II cells.…”
Section: Discussionmentioning
confidence: 99%
“…By using cDNA microarrays (25)(26)(27)(28)(29)(30)(31)(32) and proteomic technologies (Refs. 24 and 33 and references therein), it has been possible to identify several genes and proteins that are differentially regulated as a result of adipogenesis.…”
mentioning
confidence: 99%
“…In vivo transcript profiling studies of human and murine fat tissue (28,32,38) have shown the complexity of the adipocyte transcriptome and have implicitly established that the biology of these cells has a degree of intricacy that was not expected. To date, however, only two studies have investigated the proteome of human and mouse adipose tissue; one resolved about 100 human proteins using wide IPG strips and identified 16 polypeptides by means of mass spectrometry (39), while the other resolved a considerable number of murine white adipose tissue proteins and identified 80 unique polypeptides (40).…”
mentioning
confidence: 99%